William A. Rugh (ed.): Engaging the Arab & Islamic Worlds through Public Diplomacy. A Report and Action Recommendations. (Czech Journal of International Relations, 2006)
William A. Rugh (ed.): Engaging the Arab & Islamic Worlds through Public Diplomacy. A Report and Action Recommendations. 1st ed. Washington: Washington University, 2004, 174 stran, ISBN 0-9764391-0-7 (signatura knihovny ÚMV 51 914).